PENGGUNAAN MEDIA INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 008 SUNGAI BAKAU - Muliono Muliono; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the low learning outcomes fifth grade science students at SDN 008 Sungai Bakau with an average value of 56.04 by the KKM is 70. Of the 18 students of class IV, which reached KKM as 6 students (33.33%) and 12 students (66.67%) have not yet reached the KKM. This research aims to improve science learning outcomes of students by using interactive media in learning. The research is a classroom action research conducted by two cycles. Data collection tools using observation sheet activities of teachers and students, achievement test. Using statistical data analysis is done using Microsoft Excel program. Based on the results of data processing research showed that an increase in activity of teachers from 57.14% increase to 78.57%. The increased activity of teachers has been accompanied by increased activity of students is 53.57% to 67.86%. The use of interactive media can improve student learning outcomes of the average value of the basic score 68.61 into 78.33 on two daily tests. Thus the hypothesis is proven researchKey Words: Interactive Media, learning outcomes IPA